ANALISIS KEBIASAAN MEROKOK DAN KONSUMSI OBAT ANALGETIK SEBAGAI FAKTOR RESIKO PENYAKIT GAGAL GINJAL KRONIS - Diyono Diyono (KOSALA : Jurnal Ilmu Kesehatan, 2018)
Background: Chronic Renal Failure (CRF) is a chronic degenerative disease that requires great attention. This is not only because of the ever-increasing incidence, but also because of the maintenance process that takes time and enormous expenses. Globally, nationally and regionally, chronic renal failure tends to increase. The most effective therapy for chronic renal failure is the prevention of risk factors. Objectives: Identify of smokingand analgetic drug consumption as a risk factor for chronic renal failure. Methode: This research is a correlation research with case control design. The sample were 75 case study groups and 75 control groups. Data obtained through interviews and analyzed using multiple logistic regression with SPSS series 18. Result: Smoking habit (p = 0.625) and analgetik consumption (p = 0.069 had no effect on the incidence of chronic renal failure. Conclusion: Research conclusions are smoking and analgetik consumption had no effect on the incidence of chronic renal failure Keywords: Analgetik consumption, Chronic Renal Failure, smoking